The Aspergillus fumigatus transcription factor RglT is important for gliotoxin biosynthesis and self-protection, and virulence - Ries, Laure N. A.; Pardeshi, Lakhansing; Dong, Zhiqiang; Tan, Kaeling; Steenwyk, Jacob L.; Colabardini, Ana Cristina; Ferreira Filho, Jaire A.; de Castro, Patricia A.; Silva, Lilian P.; Preite, Nycolas W.; Almeida, Fausto; de Assis, Leandro J.; et al. (PLoS pathogens, 2020)
Aspergillus fumigatus is an opportunistic fungal pathogen that secretes an array of immune-modulatory molecules, including secondary metabolites (SMs), which contribute to enhancing fungal fitness and growth within the mammalian host. Gliotoxin (GT) is a SM that interferes with the function and recruitment of innate immune cells, which are essential for eliminating A. fumigatus during invasive infections. We identified a C6 Zn cluster-type transcription factor (TF), subsequently named RglT, important for A. fumigatus oxidative stress resistance, GT biosynthesis and self-protection. RglT regulates the expression of several gli genes of the GT biosynthetic gene cluster, including the oxidoreductase-encoding gene gliT, by directly binding to their respective promoter regions. Subsequently, RglT was shown to be important for virulence in a chemotherapeutic murine model of invasive pulmonary aspergillosis (IPA). Homologues of RglT and GliT are present in eurotiomycete and sordariomycete fungi, including the non-GT-producing fungus A. nidulans, where a conservation of function was described. Phylogenetically informed model testing led to an evolutionary scenario in which the GliT-based resistance mechanism is ancestral and RglT-mediated regulation of GliT occurred subsequently. In conclusion, this work describes the function of a previously uncharacterised TF in oxidative stress resistance, GT biosynthesis and self-protection in both GT-producing and non-producing Aspergillus species.